2006
DOI: 10.1002/chem.200500466
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Applications of β‐Fluoroalkylated α,β‐Unsaturated Carbonyl Compounds

Abstract: Beta-fluoroalkylated alpha,beta-unsaturated carbonyl compounds constitute efficient building blocks for the synthesis of complex fluorinated compounds. As the fluorinated moiety generally increases their reactivity, it also brings important modifications which can change the chemical behavior and selectivity. Their use has been already largely demonstrated. Nevertheless, the synthetic potential has not yet been fully explored and, consequently should play an important role in the design of new sophisticated fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…It serves as an important building block for further functionalization and an excellent substrate for cross-metathesis in various polymerization, biological, and medical applications. [1][2][3][4] The fission of the C−Cl bond of CH 2 CHC(O)Cl produces Cl atom and C 2 H 3 CO radical, a crucial intermediate that has been proposed in reactions between O atom and propargyl (C 3 H 3 ) radical in combustion and atmospheric chemistry. 5 Extensive experimental investigations on CH 2 CHC(O)Cl have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…It serves as an important building block for further functionalization and an excellent substrate for cross-metathesis in various polymerization, biological, and medical applications. [1][2][3][4] The fission of the C−Cl bond of CH 2 CHC(O)Cl produces Cl atom and C 2 H 3 CO radical, a crucial intermediate that has been proposed in reactions between O atom and propargyl (C 3 H 3 ) radical in combustion and atmospheric chemistry. 5 Extensive experimental investigations on CH 2 CHC(O)Cl have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, after several contributions from our laboratory and from others [14], this work demonstrates again that bperfluoroalkylated enones are very powerful tools and very valuable building-blocks for the synthesis of various fluorinated products, and especially heterocyclic ones, which could find highly interesting applications in the design of bioactive molecules. There is no doubt that several other properties of these building-blocks have to be exploited.…”
Section: Resultsmentioning
confidence: 80%
“…experiments revealed that the LUMO energy level of the fluorinated α,β-unsaturated carbonyl compound was lower than that of the non-fluorinated one which indicates the feasibility for higher reactivity of these fluorinated building blocks. [196][197][198][199] To this end, for the first time, Yu et al, in 2016, showed the conjugate addition of β-CF 3 enone 283 with arenes under Rh(III) catalysis and redox neutral conditions. Pyridine 282 as a directing group was used for the reaction to obtain the conjugated trifluoromethyl alkylated compounds 284 in good to high yields as shown in Scheme 52.…”
Section: Ethylbromodifluoroacetate As a Building Blockmentioning
confidence: 99%